The Political Economy of Government Responsiveness: Theory and Evidence from India - Besley, T.; Burgess, R. (Quarterly Journal of Economics, 2002)
The determinants of government responsiveness to its citizens is a key issue in political economy.Here we develop a model based on the solution of political agency problems.Having a more informed an politically active electorate strengthens incentives for governments to be responsive.This suggests that there is a role both for democratic institutions and the mass media in ensuring that the preferences of citizens are reflected in policy.The ideas behind the model are tested on panel data from India.We show that public food distribution and calamity relief expenditure are greater, controlling for shocks, where governments face greater electoral accountability and where newspaper circulation is highest.